The Effect of Free Cash Flow to Equity, Price/Earning Ratio and Profitability on Stock Prices of the Financial Sector Listed on The Idx Period 2022-2025 - Alifia Salsabila; Ati Sumiati; Dwi Kismayanti Respati (Research Trend in Technology and Management, 2025)
This study aims to examine the effect of free cash flow to equity, price/earnings ratio, and profitability on stock prices in the financial sector listed on the Indonesia Stock Exchange (IDX) during the 2022-2025 period. The research method used is a quantitative method with secondary data in the form of financial reports obtained from the Indonesia Stock Exchange website. The research sample consisted of 35 financial companies selected using a purposive sampling technique. Data analysis techniques used were classical assumption testing, descriptive statistical analysis, multiple linear regression testing, and partial and simultaneous hypothesis testing. The results show that partially, free cash flow to equity and price/earnings ratio have no effect on stock prices, while profitability is proven to influence stock prices. Meanwhile, price/earnings ratio and profitability are proven to influence stock prices simultaneously. The contribution of free cash flow to equity, price/earnings ratio, and profitability variables in influencing stock prices is 24%.